Fine particulate matter and depressive symptoms in children: A mediation model of physical activity and a moderation model of family poverty - Young Sun Joo; Jisun Kim; Jungae Lee; Ick-Joong Chung (Elsevier, 2022)
Rationale: Exposure to fine particulate matter has adverse effects on mental health outcomes. However, no empirical study has yet been conducted on mechanisms of how and why exposure to fine particulate matter can affect mental health outcomes, especially focusing on children. In addition, children living in poverty may be more vulnerable to fine particulate matter. Objective: This study aims to examine whether physical activity can explain the impact of ambient fine particulate matter on depressive symptoms among Korean children and whether family poverty moderates the associations between fine particulate matter, physical activity, and children's depressive symptoms. Methods: Children and their primary caregiver data were drawn from the Children's Happiness Life Time Survey data collected by Child Fund Korea, and fine particulate matter data were derived from Air Korea, collected by the Korea Environment Corporation. Individual-level data were linked to a nationwide neighborhood-level data on air quality. Multilevel structural equation modeling was used to consider the hierarchical data structure. The analytical sample consisted of 4,161 children living in 79 neighborhoods. Results: The findings suggest that living in neighborhoods with higher levels of fine particulate matter is associated with a decrease in physical activity, which in turn increases children's depressive symptoms. Physical activity fully mediates the association between fine particulate matter and children's depressive symptoms. However, family poverty does not have a significant moderating role for the associations between fine particulate matter, physical activity, and children's depressive symptoms. Conclusions: The results of this study indicate the importance of physical activity in relation to fine particulate matter and children's depressive symptoms.